Human genome variation - Frazer, Kelly (Henry Stewart Talks, 2007)
DNA polymorphisms in the human genome, Identification of a large number of common Single Nucleotide Polymorphisms (SNPs), The relationship of these common SNPs in linkage disequilibrium bins, The majority of common deletion polymorphisms in humans are in linkage disequilibrium with common SNPs
Archived at 2018/05/31